Lige for lige? Kønssegregering i Folketingsudvalg og i ledelsen af det private erhvervsliv - Fiig, Christina; Verner, Mette (Politik, 2016)
In this article, we describe and discuss the vertical and horizontal gender segregation in the elites of Danish Parliamentary politics and private business. Our new data on the gender distribution on corporate boards of publicly traded firms show how women are absent among board chairs and CEOs and illustrates the low representation of women among board members. Among members of Parliamentary committees a more equal gender representation is found, however, there is a clear tendency toward a vertical and a horizontal segregation. Our findings show that women MPs are less represented in certain Parliamentary committees on foreign affairs, economy, finance, tax and transportation. This distribution mirrors other country studies on Parliamentary committees. We propose two hypotheses in order to explain our explorative study: a thesis on a gender bias of certain policy areas and a hypothesis on the significance of the ‘public eye’. Concerning the latter, our results illustrate how institutions subject to ‘the public eye’ have more balanced gender compositions than institutions with less public attention, like corporate boards.